Invisible to the state. An initial estimate of “administrative disappearances” in the Brussels-Capital Region - Jacques Moriau; Alain Malherbe; Jean-Paul Sanderson; Adèle Pierre; Alexandre Leclercq (Brussels Studies)
In Belgium, having a home address allows access to fundamental rights through registration in the national register. The national register centralises all of the data collected by the municipalities. Administrative invisibilisation therefore has a direct impact on the take-up of social rights. It has three distinct origins: failure to register, deregistration and removal of persons from the national register. Based on an analysis of national register data, this article looks at the phenomenon of "administrative invisibilisation", i.e. the voluntary or involuntary disappearance or removal from administrative registers. The article begins with an anthropological analysis of administrative practices with respect to people's home addresses, followed by a quantification and spatialisation of the phenomenon of administrative invisibilisation. Finally, a sociological survey of victims of administrative invisibilisation sheds light on their pathways to exclusion.